Understanding EU Funding of Anti-Trafficking Initiatives: Where is the money (not) going? - Rossoni, Isotta (Anti-Trafficking Review, 2024)
Critical trafficking scholars have questioned the staggering and ever-rising scale of financial investments in the anti-trafficking industry. While many analyses have focused on the United States, considerably less attention has been devoted to anti-trafficking funding provided by the European Union (EU). This paper draws on an analysis of the results of several EU programmes funding anti-trafficking actions during the 2014–2020 programming period. It describes the type of projects and organisations funded, the countries involved, the amounts awarded, and the potential reoccurrence of funding toward specific organisations. It also presents the findings of a survey of European NGOs working in the field of anti-trafficking to investigate approved and rejected projects, the reasons for rejection, and the key challenges faced in accessing EU funding. The overarching aim is to better understand funding trends against the backdrop of EU anti-trafficking policy priorities.